2018
DOI: 10.1159/000493764
|View full text |Cite
|
Sign up to set email alerts
|

The Chinese Linguistic Validation of the Ureteral Stent Symptom Questionnaire

Abstract: Objective: We validated the Chinese version of the Ureteral Stent Symptoms Questionnaire (USSQ) in patients with an indwelling ureteric stent. Patients and Methods: The English version of the USSQ was translated into Chinese using a multi-step process by 3 urologists and 2 independent translators. The Chinese version was validated by asking 50 patients with temporary unilateral ureteral stent to complete the questionnaire at weeks 1 and 4 after stent placement. Thirty healthy individuals without a ureteral ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…© 2020 The American Society of Transplantation and the American Society of Transplant Surgeons TA B L E 1 PS, polymeric double-J stent; US, ureteral stenosis; USSQ, Ureteral Stent Symptom Questionnaire; UV, ureterovesical junction 5. a Success was defined as stent in situ within 1 year without obstruction or obvious migration, regardless of whether it has been reinserted or not.…”
mentioning
confidence: 99%
“…© 2020 The American Society of Transplantation and the American Society of Transplant Surgeons TA B L E 1 PS, polymeric double-J stent; US, ureteral stenosis; USSQ, Ureteral Stent Symptom Questionnaire; UV, ureterovesical junction 5. a Success was defined as stent in situ within 1 year without obstruction or obvious migration, regardless of whether it has been reinserted or not.…”
mentioning
confidence: 99%
“…USSQ is utilized to assess the safety of a new stent or medications that can relieve symptoms after placement of a stent. Zhu et al and Giannarini et al showed impairment in sexual health in patients compared to that in healthy individuals at four weeks after stent placement [29,30]. By contrast, some studies showed no significant difference when comparing sexual health at the fourth week after placement with that at the fourth week after removal [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…1 Joshi developed the USSQ, an effective tool for assessing the impact of ureteral stents on patients, which has been regarded as a reliable measure of outcomes in many studies. [2][3][4][5][6][7][8][9][10][11] In the present study, we evaluated the psychometric properties of the Japanese version of the USSQ.…”
Section: Discussionmentioning
confidence: 99%
“…This tool has become the standard for the evaluation of symptoms, and the English version of the USSQ has since been translated and validated in European and Asian countries. [3][4][5][6][7][8][9][10][11] In the present study, we developed the Japanese version of the USSQ and validated its psychometric properties to determine whether it is appropriate for evaluating the outcomes of ureteral stent placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation